Principal Component Analysis: Identifiying Underlying Issues that Lead to Divorce in South Sulawesi - Purnama, Eka (Journal of Mathematics and Applied Statistics, 2024)
This study aims to analyze the various factors contributing to divorce in South Sulawesi, with the goal of identifying and understanding the underlying issues that lead to marital breakdowns in the region. Utilizing Principal Component Analysis (PCA) to reduce the variables associated with divorce, thirteen factors were examined. The analysis revealed five key components: moral issues, personal will, differences of opinion, economic challenges, and criminality. Notably, these components accounted for 82% of the variance in the data, highlighting their significance in understanding the dynamics of divorce in South Sulawesi. This research provides valuable insights for policymakers and practitioners working to enhance marital stability in the region.